¿Es OPENLDAP una buena solución libre para la centralización de usuarios? (2015)
This article establishes the state of the art about existing solutions in the market, free or licensed that allow the centralization of users, independent to the operating system they use (OS X, Windows, Linux); all of the above in a context of authorization and user authentication (AAA). There is an analysis of the use of the OpenLDAP platform as a mechanism for centralizing users, their advantages and limitations, the presentation of a design, and recommendations based on the implementation of the system in a heterogeneous infrastructure with more than three hundred (300) members.